Leading content design - McConnell, Rachel (Book Apart (Series), 2022)
Content design teams need the right conditions to thrive--but when they're hampered by bottlenecks or putting out fires, it's hard for them to do their best work, secure support, and grow strategically. Enter content operations. With smart, operational approaches, Rachel McConnell helps you identify and remove the barriers to strong, effective content work. You'll learn how to create common standards, improve collaboration, iron out wrinkles in the design process, and build advocacy--so you can lead your team with impact.